Effects of sorption and desorption of CO2 on the thermomechanical experimental behavior of HNBR and FKM O-rings - Influence of nanofiller-reinforced rubber. (May 2019) - Lainé, E.; Grandidier, J.C.; Benoit, G.; Omnès, B.; Destaing, F.
Abstract: Despite its importance in sealing, a fundamental understanding of the behavior of elastomeric O-rings in a gas environment is still incomplete. Further experimental research is needed to obtain a precise predictive model which can describe the combined effects of gases and mechanical loading. The effect of CO2 pressure (2, 4 and 6 MPa) on the mechanical compression behavior of HNBR and FKM seals at two temperatures (60 and 130 °C) is described in the paper. To evaluate the contribution of nanofiller reinforcement, experimental tests were carried out on two kinds of rubber which are reinforced or not with nanofiller (10 phr of expanded graphite). A ranking of materials was performed thanks to experimental database. HNBR seems to be the better candidate in the service conditions applied. Furthermore, the nanofillers which are introduced in the rubber can lead some damages in Rapid Gas Decompression conditions, notably when the zero pressure was applied (desorption). Highlights: This method permits the characterization the materials used in the structure obtained with industrial process. Mechanical compression tests were carried out on O-rings under CO2 pressure at two temperatures. Mechanical compression tests were carried out on O-rings after CO2 desorption. In order to improve the measurements of the local strain an in situ optical measuring system is used. The parameters of the behavior law are modified and are a function of the temperature and CO2 pressure.